(untitled) (Medical Forum Monthly, 2024)
Objective: To study C-reactive protein, D-dimer, PT and APTT in hypertensive patients. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the Pathology Department of Bacha Khan Medical College Mardan and Medical Department of MMC Teaching Hospital Mardan from June 2017 to September 2018. Materials and Methods: In this study a total of 100 hypertensive patients and 50 healthy individuals as a control group were included in the study. All patients were subjected to evaluate for CRP, D-dimer PT and APPT. Results: A total 60% of Hypertensive patients Showed Elevated CRP levels. Mean CRP levels was 2.67±0.256 mg/l significantly elevated as compared to control group .75% of the hypertensive patients also showed elevated D-dimer level. Mean D-dimer levels were 500-1000 ng/ml in 50% of patients and 1000-2000 ng/l in 25% of patients, which were significantly elevated as compared to control group. PT and APTT were also prolonged in 6% and 8% of Hypertensive patients. Mean PT and APTT were 16.525±0.253 seconds and 45.2541±0.526 seconds respectively. P value for CRP and D-dimer were p<.00235 and p<.00316 respectively Conclusion: The study concluded that hypertension is associated with significantly elevated CRP and D-dimer levels which indicate both inflammatory and Hemostatic abnormality. Prolong PT and APTT also indicate abnormality in coagulation system. Both elevated CRP and D-dimer levels are independent risk factors for cardiovascular and thromboembolic events. This gives useful information to the clinician to strictly watch the Hypertensive patients for immediate control and treatment to improve patient’s life style and reduce further complications from the disease.